ANALISIS YURIDIS SOSIOLOGIS TERHADAP PERLINDUNGAN ANAK DALAM KASUS EKSPLOITASI PEKERJA ANAK - Fatin Hamamah (Jurnal Pembaharuan Hukum, 2015)
The phenomenon of child labor is currently a problem that is difficult to overcome, child labor appears not only caused by economic factors, but also caused by environmental factors and family. The purpose of this study is to analyze and find the characteristics of child laborers who have the potential for exploitation and the role of government in handling the problem. This research uses qualitative method with data collection technique done by observation (observation), free in-depth interview and supported by literature study. The results showed that the characteristics of child labor problems are mainly related to poverty and underdevelopment. The role of government in handling the problem of child labor is to accommodate the best interests of children to save the survival of the Nation and the State through the guarantee of life protection of Indonesian children by legislative, executive or judiciary.